Selected yeast utilization and biodiversity - Valero, Eva (2005)
The use of commercial wine yeast strains as starters has been extensively generalised over the past two decades. Wine yeast strains are annually released in wineries environment and on an annual basis. However, little is known about the fate of these strains in the vineyard. To evaluate the industrial starter yeasts’ ability to survive and spread in nature, and become part of the natural microflora of musts, we have devised a large-scale sampling plan over a period of three years in six different vineyards (3 in Portugal and 3 in France). Each vineyard has used the same industrial yeast strain(s) continuously in the last 5 years. A total of 198 grape samples were collected at various distances from the wineries, before and after harvest. Towards the end of the spontaneous fermentations, the composition of the yeast flora was determined by different typing methods (PCR-amplification of ∂-sequences, pulse field electrophoresis, RFLP of mitochondrial DNA, and microsatellite typing). Among 3780 yeast strains identified, 296 isolates had a genetic profile identical to that of commercial yeast strains. For a large majority (94%), these strains were recovered at very close proximity to the winery (10-200m). Commercial strains were mostly found in the post harvest samples, reflecting immediate dissemination. Analysis of population variations from year to year indicated that permanent implantation of commercial strains in the vineyard did not occur, but instead that these strains were subject to natural fluctuations of periodical appearance/disappearance like autochthonous strains. Overall the data show that dissemination of commercial yeast in the vineyard is restricted to short distances and limited periods of times and is largely favoured by the presence of water runoff.